2007
DOI: 10.1016/j.jvs.2007.01.028
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Vascular Surgery: A Systematic Review

Abstract: Objective The objective of this systematic review is to evaluate the results of clinical studies on laparoscopic surgery for aorto-iliac disease.Methods A systematic review of the literature from 1966 to September 2006 on laparoscopic and robotic vascular surgery was performed. Only patient series containing more than 5 cases were included. Operative, clamping and anastomosis times, conversion, mortality and morbidity and hospital stay were evaluated.Results Thirty studies were identified. These were all descr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2008
2008
2011
2011

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 0 publications
0
22
0
Order By: Relevance
“…Furthermore, RALS has shown to overcome a long learning curve which is associated with laparoscopic vascular surgery (Coggia et al, 2004). Even with few numbers of patients, clamping -and anastomosis time reduced significantly after only eight patients (Diks et al, 2007). These results show that robotic assistance can help conventional vascular surgeons to start up laparoscopic surgery, even without prior extensive laparoscopic experience.…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations
“…Furthermore, RALS has shown to overcome a long learning curve which is associated with laparoscopic vascular surgery (Coggia et al, 2004). Even with few numbers of patients, clamping -and anastomosis time reduced significantly after only eight patients (Diks et al, 2007). These results show that robotic assistance can help conventional vascular surgeons to start up laparoscopic surgery, even without prior extensive laparoscopic experience.…”
Section: Discussionmentioning
confidence: 89%
“…It has been shown that RALS for aortoiliac disease is still in a very early stage. Operative times, although comparable to conventional laparoscopic series (Nio et al, 2007), still surpass those of open surgery by far. Furthermore, no research has been done to investigate the cost-effectiveness of a robotic surgical system.…”
Section: Medical Robotics 296mentioning
confidence: 85%
See 2 more Smart Citations
“…laparoscopic dissection with mini laparotomy; 2. hand-assisted laparoscopic ABF; 3. completely laparoscopic ABF; and 4. robot-assisted laparoscopic ABF [2,3].…”
Section: Introductionmentioning
confidence: 99%